PERKEMBANGAN BAYI USIA 6 BULAN DITINJAU DARI JENIS NUTRISI Development of Infants Aged 6 Months in terms the Type of Nutrition - Hidajaturrokhmah, Nur Yeny (Eduhealth, 2015)
ABSTRACTExclusive breastfeeding in Indonesia as a major nutrient for the growth of children has decreased. In fact there is a tendency to shift the use of formula milk than breastmilk in some communities. Previous studies have shown different results in preliminary studies. Exclusively breastfed babies have better development than babies who are not exclusively breastfed. The purpose of this study was to analyze the differences in develpment in 6 months old babies of exclusive breastfeeding and not exclusive breastfeeding in Puskesmas Ngasem Kediri. This study with cross sectional design obtained 68 respondents who met the inclusion criteria of 83 babies of 6 months. Data were collected through interview and quesionair. Data were analyzed using Wilcoxon Mann Whytney, and Chi Square. The results showed developmental in exclusive breastfeeding babies and not exclusive breastfeeding all normal, as many as 68 respondents (100%). But with testing activities in each aspect of the development of gross motor, fine motor, language, and social independence showed different results. There is no difference in the development of gross motor, fine motor, and social independence between the two groups. But there are differences between the language development of exclusively breastfed babies group and not exclusive breastfeeding, with the results of statistical Wilcoxon Mann Whytney test, obtained p value 0.002 (<0.05).. Conclusion: Exclusively breastfed babies have better language development compared to not exclusively breastfed babies Keywords: breastfeeding, development, babies six months